INDONESIA GOVERNMENT’S PREVENTION OF COVID-19: CRITICAL DISCOURSE ANALYSIS STUDY - Intan Siti Nugraha; Rosaria Mita Amalia (Universitas Lambung Mangkurat, 2021)
COVID-19 information is massively reported by media and social network focus not only on the spreading and infection but also on the government’s prevention in handling the pandemic. Thus this study, under Fairclough’s critical discourse analysis (CDA) and by using Appraisal System as a tool for textual analysis, is aimed to gain insight and understanding regarding how Indonesia government’s prevention of COVID-19 in the beginning of pandemic crisis are presented in media, specifically The Jakarta Post. The result shows to some extents. Firstly Appraisal System used in the text analysis level presents that the news report published by The Jakarta Post is overridden by the voice placing the government as the target of negative JUDGMENT. Secondly, Appraisal System analysis leads to explanatory critique of the news text regarding reader positioning. The lack of representations of other choice positively or neutrally on the text strongly give the dynamic-negative meaning to the target audience.